Innovation Policy in the Context of Budget Mechanism Reformation: Goals Outline and the Tools Required for Successful Implementation - Votintseva, Liudmila Ivanovna; Sozaeva, Dzhamilya Alimovna; Andreeva, Marina Yurievna (International Journal of Economics and Financial Issues, 2015)
The article covers the methodological aspects of the system program tool for innovative policy that would facilitate the implementation of national top-priority projects under the conditions of budget mechanism reformation. The practice of innovative development regional programming uses patterns, which have proven to have low efficiency and produce fragmentation rather than achieving the expected results due to the types of design implemented. Relying on the synthesis of theoretical background, empirical assessments and practical experience in applying management by objective for the region budget formation and use, the authors show how a tooling of the system program mechanism can be used to create a basis for reformatting the existing innovative development model into a desired condition, which is well balanced in respect of goals, needs and the possibilities of achieving consensus among the region entities. Keywords: regional complex models; innovation policy; fragmentarity; budget process reforming, JEL Classifications: G18; H52; O38